Pheno-morphological and biochemical characterization of root nodules and associated root nodulating bacteria from Pongamia pinnata (L.) Pierre in the arid regions of India - Vyas, Vipula; Singh, Sangeeta; Choudhary, Sunil; Bhoi, Tanmaya Kumar; Dey, Prithwiraj; Saraswat, Anuj (Frontiers in Plant Science, 2025)
IntroductionPongamia pinnata (L.) Pierre is a resilient leguminous tree valued for its biofuel potential and ability to flourish in marginal soils due to symbiotic nitrogen fixation by root-nodulating bacteria (RNB). Understanding the phenomorphological, soil, and biochemical characteristics of its associated RNB is essential for enhancing productivity in arid regions. This study aimed to characterize RNB isolates associated with P. pinnata and assess how soil properties and nodule biochemistry influence plant growth in the arid ecosystems of western Rajasthan.MethodsTwenty RNB isolates (PP-01 to PP-20) were collected from P. pinnata nodules across arid sites. Rhizospheric soil samples were analysed for physico-chemical parameters, including pH, EC, organic carbon, and nutrient contents. Nodules were examined for morphology and nitrogen-fixing activity. Biochemical profiling of isolates included phenolics, tannins, FRAP, and total antioxidant capacity. Seedling growth responses to individual isolates were evaluated under controlled conditions. Statistical analyses included multiple regression, stepwise regression, PCA, and hierarchical cluster analysis.ResultsSoils were alkaline (pH 8.2–9.1) with moderate EC (1.18–1.89 dS m-¹) and heterogeneous nutrient availability. Nodules exhibited diverse morphology with active nitrogen fixation. Seedling growth differed significantly among isolates, with PP-18, PP-19, and PP-20 showing the highest performance. Biochemical traits varied widely; isolates PP-08, PP-09, PP-14, and PP-20 demonstrated superior antioxidant activity. Multiple regression identified nitrogen, potassium, pH, organic carbon, tannin, and antioxidant content as positive contributors to growth, while phosphorus, phenol, and EC were negative predictors (R² = 0.85). Stepwise regression indicated nitrogen, pH, organic carbon, and tannin as the most influential variables (R² = 0.61). PCA explained 98.8% of the total variance and distinctly separated isolates based on biochemical and growth characteristics. Cluster analysis grouped the twenty sites into three clusters corresponding to soil fertility gradients.DiscussionThe study demonstrates that both soil nutrient status and nodule biochemical composition jointly regulate P. pinnata growth under arid conditions. High-performing isolates, particularly PP-18, PP-19, and PP-20, possess favourable physiological and biochemical attributes supportive of plant growth. The strong discriminatory power of PCA and clustering highlights the ecological differentiation among isolates across fertility gradients. These results underscore the potential of selecting site-specific, elite RNB strains to enhance P. pinnata productivity, soil fertility, and sustainable agroforestry in arid landscapes.